Enhancing Building Permit Services Efficiency through the Building Management Information System (SIMBG) - Aimi, Nurul; Syafril, Rizki (Journal of Educational Management Research, 2025)
This study investigates the efficiency of Building Permit Services (PBG) through the Digital Platform for Building Permit Services (SIMBG), addressing increasing building regulation violations and a decline in PBG applications since the dare system's introduction. Public complaints further emphasize the need for improvement. Using a descriptive qualitative approach, data were gathered through field observations, interviews, and documentation with purposive sampling. Data analysis included reduction, visualization, and inference with source triangulation for validity. The findings show that SIMBG has not fully optimized service efficiency, especially in service time, due to technical issues and limited human resources. To improve efficiency, active coordination between central and regional governments, staff competency enhancements, dare consultation features, and regular evaluations of operating procedures are essential. The implications for educational management highlight the importance of digital transformation in streamlining administrative processes. Improving service delivery through digital platforms like SIMBG offers lessons for educational institutions to enhance efficiency. The study encourages educational leaders to focus on resource management, staff training, and continuous evaluation, ensuring efficient systems that benefit both staff and stakeholders.